Comparative Experimental and Numerical Study of Wave Loads on A Monopile Structure Using Different Turbulence Models - Zeng, Xin meng; Shi, Wei; Michailides, Constantine; Wang, Kai; Li, Xin (My University, 2021)
This study numerically and experimentally investigates the effects of wave loads on a monopile-type offshore wind turbine placed on a 1: 25 slope at different water depths as well as the effect of choosing different turbulence models on the efficiency of the numerical model. The numerical model adopts a two-phase flow by solving Unsteady Reynolds-Averaged Navier-Stokes (URANS) equations using the Volume Of Fluid (VOF) method and three different k — ω turbulence models. Typical environmental conditions from the East China Sea are studied. The wave run-up and the wave loads applied on the monopile are investigated and compared with relevant experimental data as well as with mathematical predictions based on relevant theories. The numerical model is well validated against the experimental data at model scale. The use of different turbulence models results in different predictions on the wave height but less differences on the wave period. The baseline k — ω turbulence model and Shear-Stress Transport (SST) k — ω turbulence model exhibit better performance on the prediction of hydrodynamic load, at a model-scale water depth of 0.42 m, while the laminar model provides better results for large water depths. The SST k — ω turbulence model performs better in predicting wave run-up for water depth 0.42 m, while the laminar model and standard k — ω model perform better at water depth 0.52 m and 0.62 m, respectively.
Keywords: Hydrodynamic loads; Monopile structure; Morison equation; Numerical wave tank; Turbulence models; Wave run-up